THE IMPACT OF FINANCIAL LEVERAGE ON ROE FOR ISLAMIC BANKS IN ASIAN REGION: THE STUDY BASED ON SIGNALING THEORY - Rahim, Abdul; Ashraf, Shagufta; Iftikhar, Waqas Iftikhar; Mehmood, Mr. Shahid; Khan, Dr. Muhammad Muddassar; Siddique, Dr. Muhammad (The journal of contemporary issues in business and government, 2021)
The study is designed to determine the effects of financial leverage on banks performance, further this study is based on the Islamic banks in the Asian region. The data of twenty-five Islamic Banks are chosen from Asian countries and data collected for the study is for time period (2010 -2019), and data collection was done by accessing Thomson Reuters Data Stream. Latest version of E-views is used for analyzing the data of current study. Descriptive Statistics, Correlation Analysis, Common Effect Model, Fixed Effect Model, Likelihood Test, Random effect Model and Hausman Test, are used in data analysis of the current study. Researcher used the fixed effect regression model. Results of current study revealed positive impact of Leverage on performance of Islamic Banks operating their businesses in Asian Region. Further results showed positive impact for Islamic banks performance (ROE) in the presence of control variables (Bank Size and Bank Efficiency). Findings also revealed the high financial leverage increases the performance of Islamic banks in Asian countries. The results are opposite to the thematic approach of Agency Cost Theory. Agency Cost Theory is describing that when there is increase in the equity of banks this will have negative outcomes for firm value. However, Signaling Theory is fully supporting the results of the current study. According to Signaling Theory, if there is higher capital then the performance of the banks will be much better. In current research it is found that financial leverage is on the level in Islamic Banks that totally depends upon the flexibility ratio for the adjustment of the value of debt and their power of earning.